PENGARUH PERSEPSI NILAI PELANGGAN DANPOTONGAN HARGA TERHADAP KEPUTUSANPEMBELIAN LAYANAN PREMIUM APLIKASI MUSICSTREAMING SPOTIFY(Studi Kasus Pengguna Spotify Cibinong Kab. Bogor) - Paksi Megantoro (2021)
The purpose of this study is to prove that there are effects of perceived value and price discount on purchase decision. This research uses primary sources of data. The object of this research are Spotify users who reside or currently live in Cibinong, Kab. Bogor. This research used 113 samples with accidental sampling technique. The data analysis technique used is descriptive and essential data analysis. Based on the result of data processing through t-statistics test on SmartPLS 3.0, it can be shown that perceived value and price discount have significant effects on purchase decision with significance values of 5,913 dan 13,363, respectively. This indicates that Spotify should keep up their perceived value and improve their sales promotion using price discount to increase their premium sales.